Physiological demands and impact of a simulated beach volleyball tournament on elite male and female athletes - Harat, I. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Beach Volleyball (BVB) is a high intensity sport that requires sprinting and jumping. A BVB tournament often involves several consecutive days of multiple games a day, separated by as few as 2 hours, in which case fatigue might impair performance.